2012
DOI: 10.1029/2012je004181
|View full text |Cite
|
Sign up to set email alerts
|

Aluminum abundance on the surface of Mercury: Application of a new background‐reduction technique for the analysis of gamma‐ray spectroscopy data

Abstract: [1] A new technique has been developed for characterizing gamma-ray emission from a planetary surface in the presence of large background signals generated in a spacecraft. This technique is applied to the analysis of Al gamma rays measured by the MESSENGER Gamma-Ray Spectrometer to determine the abundance of Al on the surface of Mercury. The result (Al/Si = 0.29 À0.13 +0.05 ) is consistent with Al/Si ratios derived from the MESSENGER X-Ray Spectrometer and confirms the finding of low Al abundances. The measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 41 publications
4
28
0
Order By: Relevance
“…Using the evidence for only a limited amount of global contraction (Δ R p ≤5 km) after the end of the late heavy bombardment as principal constraint and a minimal requirement on the production of secondary crust (at least 5 km), we extracted a small subset of admissible solutions whose characteristics enables us to draw the following conclusions that are robust within the assumptions of our models: Using a mantle thickness of 400 km, corresponding to the most likely value predicted by Hauck et al [], about 1% of the models tested is compatible with the imposed constraints. A larger thickness of 500 km, corresponding to the upper limit provided by Hauck et al [], delivers similar results, while a thickness of 300 km, corresponding to the lower end of the spectrum of possible interior structure configurations, seems unlikely since no admissible combination of parameters is found that satisfies the contractional and crustal production constraints simultaneously; Assuming the surface concentration of radiogenic elements measured via Gamma‐ray spectroscopy [ Peplowski et al , ] to be representative for the entire crust, we determined enrichment factors between 2.5 and 4.5, which, with 35–62 ppb Th, 20–36 ppb U, and 290–515 ppm K, hint at a bulk heat source content similar to that of the other terrestrial planets; Even though combinations of parameters for which present‐day crustal thicknesses as large as 80 km are possible, the vast majority of admissible solutions predicts the existence of a thin crust of ∼20 km or less; While it is common to find models characterized by a prolonged phase of volcanic activity as required by the observations [e.g., Head et al , ], models showing present‐day mantle convection are rare. Convective heat transport generally tends to cease after 3–4 Gyr, suggesting that Mercury may no longer be dynamically active; The 2‐D and 3‐D simulations confirm the general trends observed in the parametrized 1‐D models in terms of Mercury's thermal history and crustal production.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using the evidence for only a limited amount of global contraction (Δ R p ≤5 km) after the end of the late heavy bombardment as principal constraint and a minimal requirement on the production of secondary crust (at least 5 km), we extracted a small subset of admissible solutions whose characteristics enables us to draw the following conclusions that are robust within the assumptions of our models: Using a mantle thickness of 400 km, corresponding to the most likely value predicted by Hauck et al [], about 1% of the models tested is compatible with the imposed constraints. A larger thickness of 500 km, corresponding to the upper limit provided by Hauck et al [], delivers similar results, while a thickness of 300 km, corresponding to the lower end of the spectrum of possible interior structure configurations, seems unlikely since no admissible combination of parameters is found that satisfies the contractional and crustal production constraints simultaneously; Assuming the surface concentration of radiogenic elements measured via Gamma‐ray spectroscopy [ Peplowski et al , ] to be representative for the entire crust, we determined enrichment factors between 2.5 and 4.5, which, with 35–62 ppb Th, 20–36 ppb U, and 290–515 ppm K, hint at a bulk heat source content similar to that of the other terrestrial planets; Even though combinations of parameters for which present‐day crustal thicknesses as large as 80 km are possible, the vast majority of admissible solutions predicts the existence of a thin crust of ∼20 km or less; While it is common to find models characterized by a prolonged phase of volcanic activity as required by the observations [e.g., Head et al , ], models showing present‐day mantle convection are rare. Convective heat transport generally tends to cease after 3–4 Gyr, suggesting that Mercury may no longer be dynamically active; The 2‐D and 3‐D simulations confirm the general trends observed in the parametrized 1‐D models in terms of Mercury's thermal history and crustal production.…”
Section: Discussionmentioning
confidence: 99%
“…In all models, a primordial crustal thickness of 5 km was considered in which heat sources are enriched by a factor Λ with respect to the primitive mantle. For a given value of Λ, heat production in the primitive mantle, expressed in W/kg, is given by H0=1normalΛi=13Hiexp(λifalset¯),where H i are the heat production rates associated with all relevant radioactive species (i.e., K, Th, and U) using the abundances of Peplowski et al [] (see Table ), λ i are the corresponding decay constants, and falset¯=4.53.0235ptGyr. From mass‐balance considerations, the heat production in the mantle can then be calculated from Hm=()1+Rp3Rcr3Rcr3Rc3ρcrρm(1normalΛ)H0,where R cr is the radius of the base of the crust.…”
Section: Theory and Modelsmentioning
confidence: 99%
“…Evidence of flood volcanism, eroded flow channels, and a dearth of volcanic edifices point to low magma viscosities [ Head et al , : Byrne et al , ], which likely result from high degrees of partial melting and high lava eruption temperatures. Major element abundances inferred from MESSENGER's X‐Ray Spectrometer [ Nittler et al , ; Weider et al , ] and Gamma‐Ray Spectrometer [ Peplowski et al , ; Evans et al , ] are intermediate between low‐Fe basaltic and komatiitic compositions [ Nittler et al , ; Charlier et al , ]. Such compositions are broadly comparable to that of a high‐degree melt of enstatite chondrite material, although the low‐Fe abundance on Mercury is still higher than that of enstatite chondrite melts [ Weider et al , ; Stockstill‐Cahill et al , ].…”
Section: Constraints On Mercury's Interior Structurementioning
confidence: 99%
“…XRS and Gamma Ray and Neutron Spectrometer (GRNS) measurements of the MESSENGER mission have provided maps of Mercury's surface composition (L. Evans et al, ; Nittler et al, ; Weider et al, ; Weider et al, ; Weider et al, ; Peplowski et al, ; Peplowski, Lawrence, et al, ; Peplowski, Rhodes, et al, ; Vander Kaaden et al, ). The IcP‐HcT terrains have on average higher S/Si, Mg/Si, and Ca/Si but lower Al/Si than the smooth plains.…”
Section: Discussionmentioning
confidence: 99%
“…The surface of Mercury appears to be mostly of volcanic origin (Denevi et al, ; Head et al, ). Analysis of the data from the Gamma‐Ray spectrometer (GRS) and X‐Ray Spectrometer (XRS) onboard the MErcury Surface, Space ENvironment, GEochemistry and Ranging (MESSENGER) spacecraft (Solomon et al, ) provided geochemical maps of Mercury's surface (Evans et al, ; Nittler et al, ; Peplowski et al, ; Peplowski et al, ; Peplowski et al, ; Weider et al, ; Weider et al, ; Weider et al, ). Several distinct geochemical terrains have been identified from these maps (e.g., Weider et al (),Charlier et al (),Namur et al (),Namur and Charlier (),Vander Kaaden et al ()).…”
Section: Introductionmentioning
confidence: 99%